2013
DOI: 10.1007/s11274-013-1471-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Bacillus amyloliquefaciens against infections of Citrus aurantium seedlings by Phoma tracheiphila

Abstract: Isolate TEB1 an antagonistic endophytic bacterium, obtained from citrus leaves and identified as Bacillus amyloliquefaciens by 16S rDNA sequencing, was used for the biological control of mal secco disease of Citrus aurantium seedlings caused by the mitosporic fungus Phoma tracheiphila. The isolate TEB1 exhibited a good in vitro activity against P. tracheiphila in dual cultures as well as with the well diffusion method. C. aurantium seedlings watered with a suspension of TEB1 cells showed a reduction of 53.61 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…At this time, the crude lipopeptide extract inhibited the germination of P. tracheiphila conidia by 50 and 90% at MIC values around 47.5 and 100 μg ml −1 , respectively. These data supported our previous observations about the putative involvement of lipopeptide of TEB1 supernatant .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At this time, the crude lipopeptide extract inhibited the germination of P. tracheiphila conidia by 50 and 90% at MIC values around 47.5 and 100 μg ml −1 , respectively. These data supported our previous observations about the putative involvement of lipopeptide of TEB1 supernatant .…”
Section: Discussionsupporting
confidence: 93%
“…Recently we reported that a B. methyltrophicus TEB1strain harboring non‐ribosomal peptide synthetase genes reduced mal secco disease in vitro and in vivo , likely by inhibition of the growth of P. tracheiphila mycelium. In the present study, we investigated the time‐course production and analysis of TEB1 lipopeptides using ESI‐MS.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the isolation, identification, and characterization of microorganisms with biocontrol potential and able of colonize, endure, and be adapted to a complex niche such as the rhizosphere constitute an interesting disease management strategy. The utilization of biological control agents (BCAs) to suppress pathogens has been studied in several pathosystems involving woody plants (e.g., Pliego and Cazorla, 2012 ; Kalai-Grami et al, 2014 ), although it has been implemented to a lesser extent compared to herbaceous species, annual crops, and seedlings (Cazorla and Mercado-Blanco, 2016 ). Moreover, available information on the diversity and structure of microbial communities associated with woody plants is scant (e.g., Aranda et al, 2011 ; Zarraonaindia et al, 2015 ), particularly at the nursery propagation stage (Sun et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an isolate of B. amyloliquefaciens, named TEB1, showed in C. arantium antagonist effect against P. tracheiphila, reducing conidia germination by 55%. These results suggest that lipopeptides produced by TBE1 drive the pore formation in the fungus cytoplasmic membrane, proving to be a potential candidate for the biological control of citrus MSD [48].…”
Section: Msd In Citrus Genusmentioning
confidence: 82%
“…Complete eradication of the tree is necessary when the systemic invasion activities [57]. As reported in several pathosystems [43,44], the biological control using antagonist endophytic microorganisms could be an alternative strategy against MSD [21,48,58,59]. In particular endophytic bacteria, such as Bacillus species, the most common endophytic bacteria, induce plant resistance against several diseases [45], including vascular plant pathogens [47].…”
Section: Msd In Citrus Genusmentioning
confidence: 99%